Breeding biology of the African Pygmy Falcon: long-term variation and seasonal decline in breeding performance of an arid zone raptor - Olubodun Olufemi P; Lowney Anthony M; Bolopo Diana; Thomson Robert L (SPRINGER HEIDELBERG, 2025)
Birds of prey are apex predators and understanding their life history can serve as a valuable baseline for investigating their ecological role. Pygmy Falcons (Polihieraxsemitorquatus), Africa's smallest diurnal raptor, have evolved to be obligate associates of Sociable Weaver (Philetairussocius) colonies throughout their southern African range. As a predator, Pygmy Falcons likely impact prey communities in this system including their host and other colony associates. However, no study has explored their breeding biology in detail using long-term data. We provide results from 10 years of data collected between 2011 and 2020. We followed 66 unique Pygmy Falcon territories and 323 breeding attempts in the Kalahari, South Africa. We explored annual variation in the population density of Pygmy Falcons and investigated between- and within-season variation in reproductive investment and output. The highest average density was recorded in 2015 and the lowest in 2019 and 2020. Our results show that the breeding occurs between early austral spring (August) and late summer (February), with a peak from September to December. The maximum and most frequent clutch size was three eggs and falcons usually initiated only one breeding attempt (but up to three) in a season. The incubation and nestling periods lasted on average 33 (+/- SD 4) and 37 (+/- 5) days, respectively. A three-egg clutch size and number of fledglings produced varied between seasons, and breeding success showed a seasonal decline across the breeding season. Falcons were 7 times less likely to lay a 3-egg clutch in 2019 than in 2011 and 2012, and breeding attempts initiated in September were 3.4 times more likely to be successful than those initiated in November. Predation accounted for 49.5% of breeding failures. Our results show significant variation in the breeding parameters of these falcons, but further studies are needed to understand what drives these variations.